The Role Of Islamic Religious Education Teacher In Overcoming Youth Determination At Rembang State Vocational School - Abdul Khakim; Mochamad Fajrin; Mohammad Ghofar Abdul Ghany; Riza Ayu Dewi Jayanti; Lestari Budianto (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
Juvenile delinquency is a serious problem, because if it is done repeatedly, it will eventually have a fatal impact and harm oneself and even others. Because of these problems, it raises questions about the role and contribution of Islamic religious education teachers in dealing with juvenile delinquency that occurs in schools. This type of research is a case study with a descriptive qualitative approach. Data collection techniques using interviews, observation, and documentation. The data analysis technique is according to Milles and Huberman's opinion with three stages, namely data reduction, data display, then conclusion. In overcoming juvenile delinquency, PAI teachers have a role. First, PAI teachers provide good motivation and role models and position themselves as parents. Second , PAI teachers provide guidance on good religious and moral values, and provide approaches so that students can share about the problems they face. Third, PAI teachers teach Islamic religious values. Fourth, PAI teachers master science, train and familiarize students with applying Islamic values which are manifested in daily behavior.